The evolution of performance metrics in the competitive arena of freestyle wrestling Olympic finalists - Latyshev S. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to examine the evolution of performance metrics for wrestlers in the discipline of freestyle wrestling at the Olympic Games, both before and after the rule modifications implemented in 2013.